The crystal structure of (4-([2,2′:6′,2″-terpyridin]-4′-yl)phenyl)boronic acid, C21H16BN3O2 - Shi Wenjing; Wang Jun (Zeitschrift für Kristallographie - New Crystal Structures)
C21H16BN3O2, orthorhombic, Pna21 (no. 33), a = 28.297(6) Å, b = 6.2978(13) Å, c = 9.6279(16) Å, V = 1715.8(6) Å3, Z = 4, R gt (F) = 0.0586, wR ref (F 2) = 0.1643, T = 293 K.